Implikasi Program Makan Bergizi Gratis terhadap Keberlangsungan Usaha Pedagang Kaki Lima di Lingkungan Sekolah - Mica Siar Meiriza; Natalya Anabel Manik; Armalia Mawarni; Rizqi Alhaq; Fran Mendrova Mikael; Zahira Annisa Fadina; Chairuna Ikhwani Br Nadeak; Jilika Putri Grasela Manullang; Yemima Nainggolan (Universitas Negeri Medan, 2026)
The Free Nutritious Meal Program (MBG) is an Indonesian government policy launched on January 6, 2025, to improve the nutrition of students from early childhood education (PAUD) to high school/vocational school (SMA/SMK) levels. This study aims to analyze the impact of the MBG Program on the income and business sustainability of street vendors (PKL) in the SMKN 1 Percut Sei Tuan neighborhood, Deli Serdang Regency, North Sumatra. The study was conducted from February to April 2026 using a descriptive qualitative approach with data collection techniques through semi-structured interviews and observations of ten vendors selected by purposive sampling. Data analysis was conducted using the Miles and Huberman model with triangulation techniques to maintain data validity. The results showed that all informants experienced a significant decrease in income after the implementation of the MBG program, with decreases ranging from 35% to 70%. The greatest impact was felt by vendors selling heavy meals, while beverage and snack vendors experienced relatively mild decreases. In addition, there was a shift in the consumer base from students to the surrounding community, as well as the emergence of various adaptation strategies such as product innovation and the use of digital platforms. This study concludes that the MBG program has unintended secondary impacts on street vendors (PKL), necessitating a more inclusive policy that considers the sustainability of small-scale economic actors around schools.